A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil - Orsetti, Artur; Lopes-Andrade, Cristiano (Zootaxa, 2016)
Pelecium Kirby is the most diverse Peleciini genus, with 33 species shared between two subgenera: Pelecidium Straneo & Ball, which comprises three species, and Pelecium, with the remaining 30 species (Straneo & Ball 1989). They occur from Panama to middle Argentina, and adults are nocturnal and prey upon millipedes (Martinez 2005). Larvae have parasitoids habits and millipedes are their main preys. There are also records of Pelecium larvae devouring immature beetles (Salt 1928). Our aim in this study is to describe Pelecium igneus sp. nov.. Aedeagus of this species is the first described for Pelecium.